Inventory model with cash flow oriented and time-dependent holding cost under permissible delay in payments - Tripathi, R.P. (Yugoslav Journal of Operations Research; Vol 23 No 3 (2013): Vol. 23 No. 3, 2016)
This study develops an inventory model for determining an optimal ordering policy for non-deteriorating items and time-dependent holding cost with delayed payments permitted by the supplier under inflation and time-discounting. The discounted cash flows approach is applied to study the problem analysis. Mathematical models have been derived under two different situations i.e. case I: The permissible delay period is less than cycle time for settling the account, and case II: The permissible delay period is greater than or equal to cycle time for settling the account. An algorithm is used to obtain minimum total present value of the costs over the time horizon H. Finally, numerical example and sensitivity analysis demonstrate the applicability of the proposed model. The main purpose of this paper is to investigate the optimal cycle time and optimal payment time for an item so that annual total relevant cost is minimized.